Ấn phẩm hệ thống lương thực thực phẩm: Khu vực Đồng bằng sông Cửu Long, Việt Nam - Duong, Thanh Thi; Hoang, The Ky; Huynh, Tuyen Thi Thanh; Tuan, Thi Mai Phuong; Pham Thi, Huong Mai; Nguyen, Quoc Minh; Truong, Tuyet Mai; Tran, Van The; Dang, Van Pham; Bui, Thi Viet Anh; Pham, Thi Hanh Tho; Manh, Cuong Nguyen (2025)
This Food System Profile presents a comprehensive assessment of the food systems in the Mekong River Delta, a crucial agricultural region in southern Vietnam. The profile serves as a key reference to support stakeholders, including policymakers, researchers, development organizations, and local authorities, in implementing Vietnam’s National Action Plan for Food Systems Transformation towards Transparency, Responsibility, and Sustainability by 2030. It also offers a starting point for future monitoring and evaluation of food system changes. The profile examines the food system through a holistic lens, analyzing underlying drivers, food supply chains, the food environment, individual factors, and consumer behavior. It details outcomes related to residents’ diets, nutrition and health, socio-economic conditions, and environmental sustainability. Using a robust, publicly available set of quantitative indicators across all food system components, the profile highlights key notable features, trends, accomplishments, and challenges specific to the Mekong River Delta’s unique regional context. This profile will enable stakeholders to identify priority intervention areas, develop targeted policy recommendations, and track progress toward food system transformation goals. Ultimately, it provides a reliable foundation for evidence-based decision-making and coordinated action across the region’s complex food system landscape.